Annonaceae (Annona spp.) cultivated in the State of Campeche (Mexico) - Mex-Álvarez, Rafael Manuel de Jesús; Canche-Naal, Gabriela del Carmen; Guillen-Morales, María Magali; Garma-Quen, Patricia Margarita; Chan-Martínez, Roger Enrique; Ferrer-Dzul, Dylan Manuel (Journal of Ecohumanism, 2024)
Plants of the Annonaceae family have great pharmacological interest thanks to their production of cytotoxic compounds which can be used in cancer treatment. Among the plants belonging to this family, the species belonging to the genus Annona stand out because they have edible fruits which are marketed in Latin American countries. In Mexico it is common to grow plants such as Annona cherimola, Annona diversifolia, Annona lutescens, Annona reticulata, Annona squamosa and Annona muricata; The Mexican southeast, where the state of Campeche is located, is no exception; Therefore, the objective of this work was to present the main species of the Annonaceae family cultivated in the state of Campeche (Mexico).